1979
DOI: 10.1002/neu.480100407
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the neurodepressing hormone in the crayfish

Abstract: The effect of the neurodepressing hormone (NDH) was studied on different identified motoneurons in the abdominal ganglia of the crayfish Procambarus bouvieri (Ortmann). Although differences in sensitivity were apparent, all the neurons tested responded to NDH with a reduction in spontaneous firing rate, which lasted as long as NDH was present, and, depending on the concentration and time of action of the hormone, for even longer periods. NDH activity was determined in the various parts of the central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Surgical removal of crab X-organs causing continuous arrhythmic locomotory hyperactivity in crabs, and crayfish eyestalk ganglia extracts and in vitro release experiments from sinus glands eliciting inhibition of crayfish XOSG and motor neuron activities in electrophysiological assays suggested that NDH originates from the XOSG. NDH was, furthermore, found implicated in inhibitory effects on several circadian rhythms (6,126,(276)(277)(278). However, even the previously suggested and reasonably analysed small neuropeptide nature of NDH (279) was later totally questioned (280).…”
Section: Further Factors With Possible Effects On Circadian Rhythmicitymentioning
confidence: 99%
“…Surgical removal of crab X-organs causing continuous arrhythmic locomotory hyperactivity in crabs, and crayfish eyestalk ganglia extracts and in vitro release experiments from sinus glands eliciting inhibition of crayfish XOSG and motor neuron activities in electrophysiological assays suggested that NDH originates from the XOSG. NDH was, furthermore, found implicated in inhibitory effects on several circadian rhythms (6,126,(276)(277)(278). However, even the previously suggested and reasonably analysed small neuropeptide nature of NDH (279) was later totally questioned (280).…”
Section: Further Factors With Possible Effects On Circadian Rhythmicitymentioning
confidence: 99%